Enhancing Early Childhood Literacy Through Creative Learning Activities in Kualuh Leidong - Arlina (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2024)
This study explores the role of community engagement in addressing This study explores the role of creative learning activities in enhancing early childhood literacy in Kualuh Leidong, North Sumatra. Using a qualitative descriptive approach, data were collected through observations, interviews, and document analysis involving early childhood educators, parents, and school administrators. The findings reveal that creative strategies such as storytelling, music, drawing, role-playing, and the integration of local culture significantly improve children’s literacy skills, including vocabulary development, letter recognition, and verbal expression. These activities also promote social-emotional growth and increase children's motivation to learn. Despite challenges such as limited teaching resources and lack of training, educators expressed a strong interest in using creative methods more frequently. The study concludes that creative learning is a powerful tool to support early literacy, especially in rural educational settings, and recommends greater support for teacher training and community involvement to sustain its impact.